Perancangan Sistem Informasi Perencanaan Produksi (Studi Kasus: Divisi Pangan PT. XYZ) - Sulfita Aurora Zahra; Ainur Komariah; Rian Prasetyo; Sri Hartanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The rapid development of digitalization cannot be separated from the important role of an information system. Production planning process at PT. XYZ is still manual and not yet computerized. This causes production delays due to miscommunication and does not yet have a database in the system. This causes production delays due to miscommunication and does not yet have a database in the system. To overcome this, it is necessary to have a field study through interviews with staff at PT. XYZ to design information systems. The purpose of conducting research at PT. XYZ is, among others, producing a computerized production planning information system design in a database. The design of this production planning information system is made with a DFD (Data Flow Diagram) method using Odoo Software which can facilitate users in the process of delivering information between work departments in a computerized manner, reduce the number of human error problems, facilitate checking the availability of raw materials, and can shorten the flow of business processes that are currently running in a database so that the production scheduling and planning process is more effective and efficient.